Kinematics of the western Caribbean: Collision of the Cocos Ridge and upper plate deformation. (29th May 2014) - Kobayashi, Daisuke; LaFemina, Peter; Geirsson, Halldór; Chichaco, Eric; Abrego, Antonio A.; Mora, Hector; Camacho, Eduardo
Abstract Subduction of the Cocos plate and collision of the Cocos Ridge have profound effects on the kinematics of the western Caribbean, including crustal shortening, segmentation of the overriding plate, and tectonic escape of the Central American fore arc (CAFA). Tectonic models of the Panama Region (PR) have ranged from a rigid block to a deforming plate boundary zone. Recent expansion of GPS networks in Panama, Costa Rica, and Colombia makes it possible to constrain the kinematics of the PR. We present an improved kinematic block model for the western Caribbean, using this improved GPS network to test a suite of tectonic models describing the kinematics of this region. The best fit model predicts an Euler vector for the counterclockwise rotation of the CAFA relative to the Caribbean plate at 89.10°W, 7.74°N, 1.193° Ma−1, which is expressed as northwest‐directed relative block rates of 11.3 ± 1.0–16.5 ± 1.1 mm a−1 from northern Costa Rica to Guatemala. This model also predicts high coupling along the Nicoya and Osa segments of the Middle American subduction zone. Our models demonstrate that the PR acts as a single tectonic block, the Panama block, with a predicted Euler vector of 107.65°W, 26.50°N, 0.133° Ma−1. This rotation manifests as northeast migration of the Panama block at rates of 6.9 ± 4.0–7.8 ± 4.8 mm a−1 from southern Costa Rica to eastern Panama. We interpret this motion as tectonic escape from Cocos Ridge collision, redirected by collision with the North Andes block, which migrates to the northwest at 12.2 ± 1.2 mm a−1.